Repetition and not Parallelism as the Determinant of Poetry in the Hebrew Bible. A Case Study of Biblical Story of Creation (Gen 1) - Marcin Majewski (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
The article points to new research on the subject of poetics in the Bible and argues against the thesis that the basic indicator of poetry and poetic texts in the Bible is parallelism.According to the author, repetition is such an indicator. An analysis of the biblical story of creation of the world was used as the case study (Gen 1).